2014
DOI: 10.1159/000357832
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Developmental Contributions for Understanding the Organization of the Basal Ganglia

Abstract: Herein we take advantage of the evolutionary developmental biology approach in order to improve our understanding of both the functional organization and the evolution of the basal ganglia, with a particular focus on the globus pallidus. Therefore, we review data on the expression of developmental regulatory genes (that play key roles in patterning, regional specification and/or morphogenesis), gene function and fate mapping available in different vertebrate species, which are useful to (a) understand the embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 88 publications
(206 reference statements)
1
35
0
Order By: Relevance
“…By comparison with tetrapods, this Nkx2.1-labeled region is topologically the counterpart of the septopallidal region of tetrapods [Moreno et al, 2009;Medina et al, 2014]. Therefore, the nitrergic cell populations observed in the Vv in our study would correspond to the septopallidal populations observed in tetrapods ( Table 2).…”
Section: Forebrainsupporting
confidence: 52%
“…By comparison with tetrapods, this Nkx2.1-labeled region is topologically the counterpart of the septopallidal region of tetrapods [Moreno et al, 2009;Medina et al, 2014]. Therefore, the nitrergic cell populations observed in the Vv in our study would correspond to the septopallidal populations observed in tetrapods ( Table 2).…”
Section: Forebrainsupporting
confidence: 52%
“…See online version for colors and list for abbreviations. From this comparison, it appears that the Ceov is rather aligned with the radial dorsal part of the Pa (Pad), which includes the BSTL at a periventricular position (note that the GP is not a reference, since in birds it is displaced dorsally, as explained in Puelles et al [2007]; Abellán and Medina [2009] and Medina et al [2014]). It would be interesting to study what led the striatal cells of the Ceov to migrate ventrally during development, and what advantages (if any) this might have implied.…”
Section: The Chicken Ceov Is Populated By Stv-derived Neurons Expressmentioning
confidence: 96%
“…Scattered Stv-derived cells were also observed in the globus pallidus (GP; fig. 2 c; in chicken, the GP is ectopically located within the striatal radial division Abellán and Medina, 2009;Medina et al, 2014]). …”
Section: The Chicken Stv Produces Islet1-expressing Cells For the Ovamentioning
confidence: 99%
“…The main tenets of Medina's research focuses on (1) the phylogenic conservation of the forebrain modulator systems (including cholinergic and catecholaminergic) in vertebrates and (2) strict segregation of neuronal groups within the basal ganglia and amygdalar structures, with identification of distinctive sites of their ontogenetic origin and discrete migrational paths, already defined during the early phylogeny (Medina et al, 2014). The unparalleled advances made recently in exploring the architecture and connectivity of forebrain systems, without a doubt, reflect recent developments in imaging tools and recombinant technologies that enabled tracing and visualization of individual neurons with their development and plasticity.…”
Section: Seeking Order In the 'Jumble' Of Basal Forebrain Neuronsmentioning
confidence: 99%